Ecolinguistic study on environmental discourse in senior high school (MA/SMA) Indonesian textbook - Putra, Dona Aji Karunia (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Ecolinguistics is a study of the impact of the use of language on the survival that connects humans, other organisms, and the physical environment that is normatively oriented towards preserving relationships and sustainable life. Ecolinguistics can be used as an approach to teach Indonesian as a second language for Indonesians. With an ecolinguistic approach, students are expected to be able to learn Indonesian to represent nature or the environment they face on a daily basis. This study aims to describe the form, variation, and frequency of use of environmental discourse in Indonesian language textbooks for MA/SMA students. Furthermore, this research will specifically examine the form and function of linguistic features which include lexical and semantic aspects used in environmental discourse in Indonesian language textbooks for MA/SMA students. This study used descriptive qualitative method. The data in this study are in the form of sentences, phrases, words related to the field of ecology. The data were analyzed using ecolinguistic theoretical framework and supported by discourse theory, lexicon theory, and semantic theory. The results showed that the Indonesian Language textbooks Cerdas Berbahasa Indonesia for class X, XI, and XII written by Engkos Kosasih was still lacking in presenting discourses on environmental themes. The environmental lexicon inserted in the discourses of the textbooks Cerdas Berbahasa Indonesia for class X, XI, and XII written by Engkos Kosasih are more informative or tend to introduce general and specific terms related to the environment. The most dominant lexicon used to form the value or character of caring for the environment is the type of verb.